Problems Faced by the Farmers in Integrated Plant Nutrient Management (IPNM) - Huqe, M. A. S.; Ali, M. S.; Islam, M. R.; Hosnara (International Journal of Bio-resource and Stress Management, 2023)
The purpose of this study was to investigate the farmers’ problem in using Integrated Plant Nutrient Management (IPNM) and also to explore the relationship between the selected characteristics of the farmers and problems faced by them. The study was conducted at Birol upazilla under Dinajpur district. One hundred (100) farmers were selected randomly as the sample of the study from the population of 475 farmers of the selected upazilla involved in Integrated Soil Fertility and Fertilizer Management Project. Data were collected from the sample farmers by using a pre-tested interview schedule during 25th October to 30th November, 2006. Findings revealed that more than half (51%) of the farmers faced severe problem, while 38% and 11% faced medium and low problem respectively in using IPNM. Education, innovativeness, extension contact, cosmopoliteness and knowledge on IPNM of the farmers were found to have significant negative relationship with their problem faced in using IPNM. However, age, family size, farm size, annual family income and organizational participation of the farmers had no significant relationship with their problems faced in using IPNM.